Estimates of genetic variability, heritability genetic advance and character association of oat genotypes for green fodder yield - Singh, Anjani Kumar; Wali, Pradeep; Sharma, Manmohan (Annals of Agricultural Research, 2018)
Present investigation was carried out at the Regional Agricultural Research Station, Rajouri, SKUASTJ,during Rabi-2011-12 and 2012-13. Heritability estimates varied from 7.73 for number of leaves to98.82 percent for fodder yield q/ha. Dry matter yield showed highest GCV. High to moderatelyhigh variability for GCV coupled with high estimates of heritability were observed for all thecharacters. All the traits except, number of leaves per plant, tillers per plant and days to 5 per centmaturity exhibited comparatively higher estimates of genotypic coefficient variance, heritabilityand genetic advance as percent of mean which is indicative of predominance of additive gene actionin expression of these traits therefore for these characters selection appears to be effective. Thegenetic advancement as percent mean was found to be highest for dry matter yield (39.52). Greenfodder yield had significant and positive correlation with all the traits. This study will provideopportunity to identify best genotypes to be used in breeding. Besides it helps in understanding thediversity available in the genotypes selected and helps in selection and improvement of desirabletraits to be used or transferred during crossing programme.